Os males do Brasil são: a doença como elemento distintivo da condição de ser brasileiro - Ermelinda Maria Araújo Ferreira (Estudos de Literatura Brasileira Contemporânea)
This essay was born of the intention to compare the data collections on the empirical-traditional medicine in Portugal and Brazil, on the initiative of Michel Giacometti, naturalized Portuguese, whose work, recently discovered , was collected in the volume Artes de Cura e Espanta-Males (2009), and the Brazilian writer Mário de Andrade, author of Namoros com a Medicina (1937). The similarity of these works points to the interest of these researchers on popular culture - in particular that related to the spontaneous understanding of the luso-brazilian people about the evils of body and soul, and its stigmatizing and metaphorical interpretations of illness as a social evil. From there, it was intended to make an analysis of the construction and deconstruction of Brazilian identity myths as Jeca Tatu and Macunaíma, analyzing their background in Portuguese literary imagination and its impact on modern Brazilian literature.